Model Pembelajaran PAI dengan Pendekatan Social Emotional Learning (SEL) Untuk Memperkuat Karakter dan Akhlak Mulia Siswa Sekolah Dasar - Khilmiyah, Akif (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2013)
This paper aims at assessing the superiority of Islamic education learning model (PAI) with Social and Emotional Learning (SEL) to strengthen efforts of establishing the character and moral values of primary school students. Analysis of inductive method is conducted by an in-depth literature review to discover the design of PAI learning model PAI with SEL to shaping the character and moral values of primary school students. Conclusion of this paper shows that model of Social-Emotional Learning (SEL) for PAI should be done in a holistic manner to foster emotional and social intelligence. Holistic learning occurs when PAI curriculum shows themes that encourage the exploration of the authentic and natural events. Through the themes, meaningful learning processes and materials occur that are designed to be interconnected with various areas of curriculum development in the PAI. Holistic learning approach, based on inquiry in which children are involved in planning, explores and shares ideas.